Improving Students' Ability to Write Procedure Texts Through Make A Match Learning Method In Class V11 of SMP Negeri 1 Pantai Baru - Sulla, Musa (BAHTRA: Pendidikan Bahasa dan Sastra, 2023)
Writing is one of the language skills that is often felt to be a problem for students in the English learning process. This can be seen from the results of students' learning about expressing meaning in rhetorical steps in simple short essays using a variety of written language accurately, fluently and acceptably to interact in the context of everyday life in procedural texts in semester 2 as many as 60% of students are still under KKM (minimum completeness criteria). This problem really attracted the attention of the author to try to explain the topic of analysis of students' ability to write text in the form of procedures using the make a match learning method. This classroom action research was carried out in Class VII of SMP Negeri 1 Pantai Baru with a total of 29 students. The aim to be achieved in this research is to improve students' ability to compose procedure texts, develop learning strategies and learning methods that are effective, efficient and enjoyable. Students can involve themselves actively in communication activities by expressing their ideas, opinions and feelings simply both orally and written. The technique used in this research is conducting observations and giving students performance tests in the form of written tests. From the research that has been carried out, the results of observations indicate that 19 out of 29 students (70.73%) appear active in the learning process. Only 1 student (0.22%) scored students from the written test evaluation who still did not reach the KKM (minimum completeness criteria). The students' post test scores in the form of individual evaluations via the Student Worksheet show that 3 students (0.07%) got a C 'good' score, 17 students (0.41%) got a D 'fair' score, 20 students (0.49% ) received an E 'poor' grade. Based on the results of data analysis, it was found that the research objectives that had been implemented were successful. In other words, implementing learning actions through the Make a Match learning method can improve students' ability to write procedural texts and increase student activity in the learning process